Delirium as a Presenting Feature of Occult Malignancy: A Case Report - Demkow, Sara; Sowińska, Joanna; Cieślak, Aleksandra; Paluszkiewicz, Natalia; Bryg, Sandra; Siemińska, Karolina; Kwiatkowski, Mateusz; Leżańska, Zofia; Pałyga, Emil; Marcinkowska, Katarzyna Diana (Quality in Sport, 2026)
Background: Delirium is a psychiatric syndrome prevalent in elderly patients. According to the DSM-5-TR and ICD-11 it is characterized by a disturbance in awareness, orientation and attention. Treating delirium is difficult as the underlying medical conditions are not always apparent. Etiology is heterogeneous and can be attributed to infection, electrolyte imbalances, substance withdrawal or other factors disrupting homeostasis. Aim: The aim of this case report is to highlight the importance of considering metastatic malignancy in the differential diagnosis of delirium in elderly patients. Furthermore, it underscores the value of interdisciplinary collaboration between psychiatrists and internal medicine specialists in the diagnosis and management of such cases. Materials and methods: A narrative literature review was conducted using PubMed, the WHO ICD database, Oxford University Press, and The Lancet, including meta-analyses, case reports, systematic reviews, and international treatment guidelines published up to 2025. Case presentation: This case presents an 82 year old woman admitted to the psychiatric hospital, with a preliminary diagnosis of organic mood disorder. Exhibiting visual hallucinations, suicidal thoughts, fluctuating disturbances of consciousness and delusions of persecution. During hospitalization laboratory findings revealed elevated C-reactive protein levels and leukocytosis. Broad spectrum antibiotic therapy was administered after the collection of blood and urine samples. Due to suspected somatic causes of delirium and ineffectiveness of antibiotic therapy, the patient was transferred to the internal medicine department. During further diagnostic workup, the patient was found to have metastatic cancer of idiopathic origin. Conclusions: This case report presents delirium as a possible indicator of physiological imbalance, such as a tumor, providing insight into how psychiatric symptoms may act as markers of an underlying systemic disease.